The Connection Between Recurrent Aphthous Stomatitis (RAS) and Psychological Stress in Patients at RSGM Nala Husada - Nur Tsurayya Priambodo; Kharinna Widowati; Aulia Dwi Maharani; Kurnia Hayati (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2024)
Background: The most common oral soft tissue disease at RSGM Nala Husada is recurrent aphthous stomatitis. RAS is a condition marked by inflammation of the orakl mucosa, which manifests as one or more ulcers that recur over time. RAS can be influenced by various predisposing factors, with stress being a common trigger. Stress refers to the body's reaction to challenges or pressures that lead to uncomfortable feelings, which are perceived differently by each person. Objective: To determine the relationship between stress in patients with recurrent aphthous stomatitis at RSGM Nala Husada. Materials and Methods: The population and samples of all RAS patients who visited RSGM Nala Husada were taken by purposive sampling with a total of 100 people. The level of stress experienced by a person measured from the Depresion Anxiety Stress Scale (DASS) questionnaire which consists of 42 questions. Data on RAS were taken from subjective examination and intra-oral examination. Processing of data using correlation test with Spearman test in SPSS program. Results: The results of the Spearman test are a weak correlation, which can be seen from R= 0.115 (Sig = 0.175.> 0.05). A positive R value means that the relationship is in the same direction. Conclusion: In this study there was no significant relationship between psychological stress in RAS patients at RSGM Nala Husada. Therefore, it is necessary to review further the severity, duration and intensity of stress that can trigger the emergence of RAS and reconsider other predisposing factors related to RAS besides stress.